PBT (polybutylene terephthalate) composite material as well as preparation method and application thereof

By adding bromine flame retardant, a small amount of antimony-containing flame retardant synergist and talc powder with a specific particle size distribution to the PBT composite material, the problem of degradation of flame retardant effect of antimony-containing flame retardant materials in the prior art under high temperature and high humidity environments is solved, and the good flame retardant performance and tensile strength of the material are achieved.

CN119859390APending Publication Date: 2025-04-22KINGFA SCI & TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411992006.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the prior art, the use of antimony-containing flame retardant synergist is problematic with limited resources, environmental pollution and high costs, and its flame retardant effect is easily reduced in a high temperature and high humidity environment.

Method used

By adding bromine flame retardant and a small amount of antimony-containing flame retardant synergist to the PBT composite material, and combining talc powder with a certain average particle size and particle size distribution, the flame retardant performance of the material and the performance after moisture and heat aging are improved.

Benefits of technology

The good initial flame retardant performance of PBT composite materials and the flame retardant performance after moisture and heat aging are achieved, reducing the self-degradation of the material in a humid and heat environment and maintaining high tensile strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223844040000021
    Figure BDA0005223844040000021
  • Figure BDA0005223844040000071
    Figure BDA0005223844040000071
  • Figure BDA0005223844040000072
    Figure BDA0005223844040000072
Patent Text Reader

Abstract

The invention relates to a PBT (polybutylene terephthalate) composite material as well as a preparation method and application thereof. The PBT composite material is prepared from the following components in parts by weight: 40 to 55 parts of PBT resin, 8 to 15 parts of brominated flame retardant, 0.5 to 1.6 parts of talcum powder, 25 to 35 parts of glass fiber and 1 to 2 parts of antimony-containing flame-retardant synergist. The PBT composite material disclosed by the invention has good flame retardant property, and the flame retardant property after damp-heat aging is still kept good. In addition, the tensile strength of the PBT composite material disclosed by the invention can still be kept good after damp-heat aging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer material processing, and more specifically, to a PBT composite material and a preparation method and application thereof. Background Art

[0002] Polybutylene terephthalate (PBT) is widely used as functional parts of electrical components, such as motor housings, relays, connectors, plugs and sockets, fan frames and blades of cooling fans, etc., because of its excellent electrical properties, mechanical strength, processability and electrical insulation properties. These functional parts usually have flame retardancy and high strength. The modification method for imparting flame retardancy to engineering plastics is usually to blend PBT with flame retardants and antimony-containing flame retardant synergists by extrusion. For example, a Chinese patent entitled "A low TVOC flame retardant reinforced PBT composite material and its preparation method and application" reports that a low TVOC flame retardant reinforced PBT material is obtained by using bromine flame retardants and antimony-containing flame retardant synergists.

[0003] However, antimony-containing flame retardant synergists, especially antimony white, were listed as Class 2B carcinogens by the World Health Organization's International Agency for Research on Cancer in 2017. In addition, due to limited antimony resources and the possible environmental pollution caused by the mining and production of antimony compounds, the price of antimony compounds has been rising, thereby increasing material costs. Research on antimony-free halogenated flame retardant reinforcements or reducing the synergistic use of antimony compounds has also become one of the hot research directions of flame retardant materials.

[0004] In addition, the activity of antimony-containing flame retardant synergists is easily affected by temperature and humidity. For example, if the PBT material with antimony-containing flame retardant synergists is placed in a high temperature and high humidity environment for a long time, its flame retardant effect will be significantly reduced. Summary of the invention

[0005] The primary purpose of the present invention is to overcome the technical problems that the flame retardant technology of the above-mentioned prior art is relatively lacking in antimony-free or antimony compound-reducing flame retardant technology, and the flame retardant effect of flame retardant materials containing antimony compounds is easily reduced in high temperature and high humidity environments, and to provide a PBT composite material.

[0006] A further object of the present invention is to provide a method for preparing the above-mentioned PBT composite material.

[0007] A further object of the present invention is to provide the use of the above-mentioned PBT composite material in the preparation of functional parts of electrical components.

[0008] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0009] A PBT composite material comprises the following components in parts by weight:

[0010]

[0011] The average particle size of the talc powder is 0.65-4.6 μm, and the distribution of the particle size of the talc powder is as follows: the content of talc powder with a particle size of ≤0.2 μm is less than 10 wt % and the content of talc powder with a particle size of ≥10 μm is less than 10 wt %.

[0012] The addition of glass fiber is mainly to improve the basic mechanical strength of PBT composite materials, and it also helps to improve the flame retardant properties of PBT composite materials.

[0013] The present invention adds a brominated flame retardant and a small amount of antimony-containing flame retardant synergist to the PBT resin to improve the flame retardant performance of the PBT composite material. Due to the small amount of antimony-containing flame retardant synergist added, the PBT composite material cannot reach V-0 (0.8mm).

[0014] The inventors of the present invention have found through research that the addition of talcum powder with a certain average particle size and a certain particle size distribution can not only improve the initial flame retardant properties of the PBT composite material, but also keep the flame retardant properties of the PBT composite material good after wet heat aging. The reason may be that the addition of talcum powder with a certain average particle size and particle size distribution can improve the nucleation and crystallization degree of the PBT composite material, which is beneficial to improving the flame retardant properties of the PBT composite material on the one hand, and on the other hand, it can prevent water molecules from penetrating into the PBT composite material, reduce the negative impact of moisture on the activity of the antimony-containing flame retardant synergist in a wet heat environment, and reduce the self-degradation of the PBT resin in a wet heat environment, so that the flame retardant properties of the PBT composite material after wet heat aging are kept good.

[0015] In addition, since the addition of talcum powder reduces the self-degradation degree of PBT resin in a wet and hot environment, the tensile strength retention rate of PBT composite materials after wet and hot aging is high.

[0016] In the present invention, the average particle size of talc can be 0.65, 0.7, 0.8, 0.9, 1.0, 1.2, 1.5, 2, 2.5, 3, 3.5, 4, 4.3, 4.5 or 4.6 μm. The average particle size and particle size distribution of talc can be measured by a particle size analyzer.

[0017] Preferably, the distribution of the talc powder particle size is as follows: the content of talc powder with a particle size of ≤0.2 μm is 2-7 wt %, and the content of talc powder with a particle size of ≥10 μm is 1-8 wt %.

[0018] In the present invention, the PBT resin is used as the main resin, and its content preferably accounts for more than 40 wt % of the PBT composite material.

[0019] Preferably, the intrinsic viscosity of the PBT resin is 0.8 to 1.3 dl / g.

[0020] In the present invention, the intrinsic viscosity of the PBT resin is tested according to method A (capillary viscometer method) in GB / T14190-2017.

[0021] Preferably, the brominated flame retardant is at least one of brominated epoxy, brominated polystyrene, brominated polycarbonate, decabromodiphenylethane or polypentabromobenzyl acrylate.

[0022] Preferably, the antimony-containing flame retardant synergist is at least one of antimony white or sodium antimonate.

[0023] Preferably, the average retention length of the glass fibers is 300-400 μm, and the weight percentage of glass fibers with a retention length of ≥400 μm is ≤30 wt%.

[0024] More preferably, the average retention length of the glass fibers is 300-400 μm, and the weight percentage of the glass fibers with a retention length ≥ 400 μm is 10-25 wt%.

[0025] By regulating the average retention length of the glass fiber within this range, the tensile strength retention rate of the obtained PBT composite material after wet-heat aging is higher.

[0026] Test of the average retention length and retention length distribution of glass fibers: 100 grams of PBT composite material was placed in a crucible, placed in a muffle furnace at 650°C for 2 hours, then taken out and cooled to room temperature, and then the remaining solid powder was placed on a two-dimensional microscope for observation to distinguish the length, and 1000 glass fibers were read continuously to obtain the average retention length and retention length distribution of the glass fibers after calculation.

[0027] Preferably, the glass fiber is alkali-free glass fiber.

[0028] Preferably, the glass fiber is a glass fiber modified with a coupling agent.

[0029] Preferably, the average cross-sectional diameter of the glass fiber is 5 to 18 μm.

[0030] Preferably, the PBT composite material further comprises 3 to 5 parts of a toughening agent.

[0031] More preferably, the toughening agent is at least one of ethylene-acrylate-glycidyl methacrylate terpolymer, ethylene-acrylate binary copolymer or ethylene-vinyl acetate copolymer.

[0032] Preferably, the mass percentage of the antimony-containing flame retardant synergist in the PBT composite material is 0.9-2.3%.

[0033] More preferably, the mass percentage of the antimony-containing flame retardant synergist in the PBT composite material is 0.9-1.3%.

[0034] In the case of a lower content of the antimony-containing flame retardant synergist, the PBT composite material of the present invention can still maintain good initial flame retardancy and flame retardancy after wet heat aging.

[0035] Preferably, the PBT composite material further comprises 0.3 to 1 part of other additives.

[0036] Optionally, the other auxiliary agents include at least one of a lubricant or an antioxidant.

[0037] Optionally, the lubricant is at least one of aliphatic carboxylic acid esters, erucamide, ethylene bisstearamide, montan esters, polyethylene wax or oxidized polyethylene wax.

[0038] Optionally, the antioxidant is at least one of a hindered phenol antioxidant, a phosphite antioxidant or an organic sulfur antioxidant.

[0039] The preparation method of the above-mentioned PBT composite material comprises the following steps: mixing the components, melt-extruding, and granulating to obtain the PBT composite material.

[0040] Preferably, the temperature of the melt extrusion is 200-240° C.; the screw speed of the extruder for the melt extrusion is 400-550 rpm, and the screw aspect ratio is 30-50:1.

[0041] The application of the above-mentioned PBT composite material in the preparation of functional components of electrical elements is also within the protection scope of the present invention.

[0042] Preferably, the electrical component functional part is a relay housing, a cooling fan frame blade or a connector housing.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The PBT composite material of the present invention has good flame retardant properties, and the flame retardant properties after wet heat aging are still good. In addition, the tensile strength of the PBT composite material of the present invention can still be maintained well after wet heat aging. DETAILED DESCRIPTION

[0045] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0046] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:

[0047] PBT resin 1#: TH6082, Lanshan Tunhe, intrinsic viscosity 0.82dl / g;

[0048] PBT resin 2#: TH6100, Lanshan Tunhe, intrinsic viscosity 1.0 dl / g;

[0049] PBT resin 3#: GL236, Yizheng Chemical Fiber, intrinsic viscosity 1.25dl / g;

[0050] Brominated flame retardant 1#: brominated epoxy, F-2100, ICL of Israel;

[0051] Brominated flame retardant 2#: brominated polystyrene, BPS 7010, Tianyi Chemical;

[0052] Brominated flame retardant 3#: brominated polycarbonate, BC-58, Chemtura;

[0053] Antimony-containing flame retardant synergist: antimony white, S-05N, Chenzhou Antimony Industry;

[0054] Talc A#-0: HTP2, based on mmol / l, with an average particle size of 2.4 μm.

[0055] Taking talcum powder A#-0 as raw material and passing it through different sieves, we obtain: talcum powder with a particle size distribution of ≤0.2μm, recorded as talcum powder A#-1; talcum powder with a particle size distribution of 0.2-1μm, recorded as talcum powder A#-2; talcum powder with a particle size distribution of 1-4μm, recorded as talcum powder A#-3; talcum powder with a particle size distribution of 4-10μm, recorded as talcum powder A#-4; talcum powder with a particle size distribution of ≥10μm, recorded as talcum powder A#-5; for talcum powder of a certain particle size distribution that is less in talcum powder A#-0 (for example, talcum powder with a particle size distribution ≥10μm), a sufficient usage amount can be obtained by increasing the number of sieving times.

[0056] By adjusting the mass ratio of talcum powder A#-1, talcum powder A#-2, talcum powder A#-3, talcum powder A#-4 and talcum powder A#-5 (two or more), and then mixing, talcum powders 1 to 6# with different average particle sizes and different particle size distributions are obtained; the average particle size and particle size distribution of talcum powders 1 to 6# are measured by a particle size analyzer, and the average particle size and particle size distribution of talcum powders 1 to 6# are as follows:

[0057] Talc powder 1#: average particle size is 1 μm; particle size distribution is: the content of talc powder with a particle size ≤ 0.2 μm is 5 wt% and the content of talc powder with a particle size ≥ 10 μm is 2 wt%;

[0058] Talc powder 2#: average particle size is 4 μm; particle size distribution is: the content of talc powder with a particle size ≤ 0.2 μm is 3 wt% and the content of talc powder with a particle size ≥ 10 μm is 6 wt%;

[0059] Talc powder 3#: average particle size is 0.8 μm; particle size distribution is: the content of talc powder with a particle size ≤ 0.2 μm is 20 wt% and the content of talc powder with a particle size ≥ 10 μm is 0 wt%;

[0060] Talc powder 4#: average particle size is 4.5 μm; particle size distribution is: the content of talc powder with a particle size ≤ 0.2 μm is 0 wt% and the content of talc powder with a particle size ≥ 10 μm is 15 wt%;

[0061] Talc powder 5#: average particle size is 0.2 μm; particle size distribution is: the content of talc powder with a particle size ≤ 0.2 μm is 10 wt% and the content of talc powder with a particle size ≥ 10 μm is 5 wt%;

[0062] Talc powder 6#: average particle size is 5 μm; particle size distribution is: the content of talc powder with a particle size ≤ 0.2 μm is 2 wt% and the content of talc powder with a particle size ≥ 10 μm is 10 wt%;

[0063] Other filler 1#: calcium carbonate AC-MLT04, Melite; average particle size 1.55 μm; the calcium carbonate was sieved to make its average particle size 1 μm, and the particle size distribution was: the calcium carbonate content was 5wt% when the particle size was ≤0.2 μm and the calcium carbonate content was 2wt% when the particle size was ≥10 μm, and then used.

[0064] Toughening agent: ethylene-methyl acrylate copolymer, ELVALOY AC 1125, DuPont;

[0065] Glass fiber: alkali-free glass fiber, ECS13-4.5-534A, cross-sectional diameter 13 μm, Jushi Group;

[0066] Other additives 1#: obtained by mixing antioxidant 1010, antioxidant 168 and pentaerythritol stearate (lubricant) in a mass ratio of 1:1:1. Antioxidant 1010, antioxidant 168 and pentaerythritol stearate are all commercially available products.

[0067] Unless otherwise specified, the components (such as toughening agent, other auxiliary agent 1#, etc.) selected in each parallel example and comparative example are the same commercially available products.

[0068] The properties of the PBT composite materials provided in the embodiments and comparative examples of the present invention were measured according to the following test methods:

[0069] 1. Tensile strength: including initial tensile strength and tensile strength after aging, tested according to ISO 527-2019 standard; aging treatment: 1000 hours of aging at 85°C, 85% RH according to GB / T 2423.3-2016 method, then placed at room temperature for 12 hours, and then flame retardant performance test. The tensile strength after aging is divided by the initial tensile strength to obtain the tensile strength retention rate after aging.

[0070] 2. Flame retardant performance: including initial flame retardant performance and flame retardant performance after aging; tested in accordance with UL 94-2014 standard; aging treatment: 1000 hours of aging at 85°C, 85% RH according to GB / T 2423.3-2016 method, then placed at room temperature for 12 hours, and then flame retardant performance test.

[0071] The preparation process of the PBT composite material of each embodiment and comparative example of the present invention is as follows: first, the PBT resin is placed at 130°C for drying for 3 hours; then, each component is weighed according to the ratio, mixed, and then melt-extruded in a twin-screw extruder, and granulated to obtain the PBT composite material. Wherein, the temperature of the first zone of the twin-screw extruder is 210°C, the temperature of the second zone is 210°C, the temperature of the third zone is 220°C, the temperature of the fourth zone is 220°C, the temperature of the fifth zone is 230°C, the temperature of the sixth zone is 230°C, the temperature of the seventh zone is 240°C, the temperature of the eighth zone is 240°C, the temperature of the ninth zone is 230°C, the temperature of the die head is 240°C, the main engine speed is 500 rpm, and the screw aspect ratio is 40:1.

[0072] Among them, the glass fibers of Examples 1 to 10 and the comparative examples were added from the side feed port of the 5th screw barrel of the twin-screw extruder; the glass fibers of Example 11 were added from the side feed port of the 7th screw barrel of the twin-screw extruder; and the glass fibers of Example 12 were added from the side feed port of the 8th screw barrel of the twin-screw extruder. The distribution of the retained length of the glass fibers of the PBT composite materials obtained in the examples and comparative examples was tested, as follows:

[0073] The distribution of the retained length of the glass fibers of the PBT composite materials of Examples 1, 4 to 10 and the comparative examples is as follows: the average retained length is about 300 μm, and the weight percentage of the glass fibers with a retained length ≥ 400 μm is about 18%;

[0074] The distribution of the retained length of the glass fibers of the PBT composite material of Example 2 is as follows: the average retained length is about 300 μm, and the weight percentage of the glass fibers with a retained length ≥ 400 μm is about 19%;

[0075] The distribution of the retained length of the glass fibers of the PBT composite material of Example 3 is as follows: the average retained length is about 300 μm, and the weight percentage of the glass fibers with a retained length ≥ 400 μm is about 18%;

[0076] The distribution of the retained length of the glass fibers of the PBT composite material of Example 11 is as follows: the average retained length is about 350 μm, and the weight percentage of the glass fibers with a retained length ≥ 400 μm is about 22%;

[0077] The distribution of the retained length of the glass fibers of the PBT composite material of Example 12 is as follows: the average retained length is about 370 μm, and the weight percentage of the glass fibers with a retained length ≥ 400 μm is about 28%.

[0078] Examples 1 to 12

[0079] Examples 1 to 12 provide a series of PBT composite materials, the formulations of which are shown in Table 1.

[0080] Table 1 Formulas of Examples 1 to 12 (parts by weight)

[0081]

[0082] Comparative Examples 1 to 6

[0083] Comparative Examples 1 to 6 provide a series of PBT composite materials, and their formulations are shown in Table 2.

[0084] Table 2 Formulas of Comparative Examples 1 to 6 (parts by weight)

[0085]

[0086]

[0087] The properties of the PBT composite materials of the embodiments and comparative examples were measured according to the above-mentioned test methods. The test results are shown in Table 3.

[0088] Table 3 Performance test results of PBT composite materials of various embodiments and comparative examples

[0089]

[0090] From Table 3, we can see that:

[0091] The PBT composite materials of Examples 1 to 12 all have an initial flame retardancy rating of V-0 when the amount of antimony-containing flame retardant synergist added is relatively small, and the flame retardancy rating after aging is all V-0, indicating that the PBT composite materials of the present invention have good flame retardancy, and the flame retardancy after wet heat aging is still good. In addition, the initial tensile strength of the PBT composite materials of Examples 1 to 12 is all above 112 MPa, and the tensile strength retention rate after aging is all above 93%, indicating that the tensile strength of the PBT composite materials of the present invention can still be maintained well after wet heat aging.

[0092] The average particle size and / or particle size distribution of the talc powder added in Comparative Examples 1 to 4 are not appropriate. When the amount of antimony-containing flame retardant synergist added is small, the initial flame retardant performance of the PBT composite material is not good or poor, the flame retardant grade after aging is also not good or poor, and the tensile strength retention rate after aging is low.

[0093] In Comparative Example 5, no talc was added, and the obtained PBT composite material had poor initial flame retardancy, and poor flame retardancy and tensile strength retention after wet heat aging.

[0094] Comparative Example 6 uses calcium carbonate instead of talc, and the resulting PBT composite material has poor initial flame retardancy, and poor flame retardancy and tensile strength retention after wet heat aging.

[0095] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A PBT composite material, characterized in that: The composition comprises the following components in parts by weight: The average particle size of the talc powder is 0.65-4.6 μm, and the distribution of the particle size of the talc powder is as follows: the content of talc powder with a particle size of ≤0.2 μm is less than 10 wt % and the content of talc powder with a particle size of ≥10 μm is less than 10 wt %.

2. The PBT composite material according to claim 1, characterized in that: The intrinsic viscosity of the PBT resin is 0.8 to 1.3 dl / g.

3. The PBT composite material according to claim 1, characterized in that: The brominated flame retardant is at least one of brominated epoxy, brominated polystyrene, brominated polycarbonate, decabromodiphenylethane or pentabromobenzyl polyacrylate.

4. The PBT composite material according to claim 1, characterized in that: The antimony-containing flame retardant synergist is at least one of antimony white or sodium antimonate.

5. The PBT composite material according to claim 1, characterized in that: The average retention length of the glass fiber is 300-400 μm, and the weight percentage of the glass fiber with a retention length of ≥400 μm is ≤30 wt%.

6. The PBT composite material according to claim 1, characterized in that: The PBT composite material also includes 3 to 5 parts of a toughening agent.

7. The PBT composite material according to claim 1, characterized in that: The mass percentage of the antimony-containing flame retardant synergist in the PBT composite material is 0.9-2.3%.

8. The PBT composite material according to claim 1, characterized in that: The PBT composite material also includes 0.3 to 1 part of other additives.

9. The method for preparing the PBT composite material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components, melt-extruding and granulating to obtain the PBT composite material.

10. Use of the PBT composite material according to any one of claims 1 to 8 in preparing functional parts of electrical components.

Citation Information

Patent Citations

  • PBT (polybutylene terephthalate) composite material as well as preparation method and application thereof

    CN114316531A

  • Good-appearance glass fiber reinforced flame-retardant PBT (polybutylene terephthalate) composition as well as preparation method and application thereof

    CN114517004A

  • PBT (polybutylene terephthalate) composite material as well as preparation method and application thereof

    CN116606533A

  • Resin composition and molded article

    JP2001181488A

  • Thermoplastic resin composition and molded product manufactured therefrom

    WO2022045616A1